Reorientation of Multicultural Education Curriculum in Indonesia: Perspective of Global Education Issues and Implications for Islamic Education Management - Iska Fatmawati; Uus Ruswandi; Atep Muhammad Lutfi; Ade Abdullah Sidiq; Eva Saufana (International Journal of Nusantara Islam, 2026)
This study aims to analyze the urgency of reorienting the Multicultural Education curriculum in Indonesia in response to global education dynamics, including curriculum decolonization and the strengthening of global citizenship. The changing paradigm of global education demands that the national education system not only emphasize knowledge transfer but also the formation of diversity awareness, social justice, and cultural identity in the context of an increasingly pluralistic society. This study uses a descriptive qualitative method and a library research approach to analyze national and international literature on the multicultural curriculum, educational globalization, and the management of Islamic education. The analysis is conducted by placing the perspective of Islamic Education Management as a conceptual framework in understanding the dynamics of curriculum change. The results show that the implementation of multicultural education in Indonesia still tends to be normative and ceremonial, limited to strengthening the value of tolerance without being followed by a more transformative reconstruction of the curriculum, learning strategies, or institutional governance. As a result, multicultural education has not fully functioned as a strategic instrument in building students' global competencies. This study introduces a novel conceptual framework for Integrative Multicultural Curriculum Reorientation that combines the perspective of global citizenship with the value of religious moderation (wasatiyah) in the governance of the Islamic education curriculum. This model emphasizes integrating diversity values, religious identity, and global competency through a systemic approach to curriculum management. Thus, reorienting the multicultural curriculum not only strengthens social cohesion in a pluralistic society but also serves as a crucial strategy for Islamic educational institutions to produce graduates who are adaptive to global challenges and firmly rooted in Islamic values.